RENAL FUNCTION IN EXPERIMENTAL HYDRONEPHROSIS - Johnson, Reuben A. (The Rockefeller University Press, 1918)
Complete obstruction of the ureter causes atrophy of the renal parenchyma, especially marked in the portions lateral to the renal sinus. The longer the duration of the obstruction, the greater is the degree of atrophy. If the obstruction is removed within 2 weeks the kidney may regain its normal structure except for a varying amount of atrophy in the lateral portions. Kidneys obstructed for 2 weeks or less may regain their normal function, as measured by the phthalein test. The longer the period of obstruction, the slower is the rate of recovery. A hydronephrosis of 7 days' duration required 40 days, and one of 14 days' duration required 152 days to recover normal function.